تقويم آليات دعم المشروعات الصغيرة والمتوسطة في سورية- دراسة ميدانية على المشروعات الصغيرة والمتوسطة في محافظة اللاذقية - مرهج, منذر; علي, مضر (Latakia University Journal - Economic and Legal Sciences Series, 2019)
This study aimed to evaluate the current mechanisms in support and development of small and medium enterprises in Syria, from the point of view of owners and managers of these Enterprise. The mechanisms of financing, technical, production, marketing, legislation and government policies have been studied and evaluated. The descriptive approach was used, The number of the distributed questionnaires and valid for the study (137) questionnaire, The data were analyzed using the statistical analysis program (SPSS). The results showed inadequate financial support mechanisms to initiate or expand the activity of the Enterprise under study, and a lack of diversity in their sources of funding. It also showed the inability of technical support mechanisms to provide the components of construction Enterprise, or reduce the time and cost of construction. It also showed the lack of legislative support mechanisms and government policies that reduce the financial burden on these Enterprise or contribute to reducing competition with large imports or Enterprise. It also showed the absence of productive support mechanisms that help to provide technological information for each industry of the Enterprise under study, or provide technical advice and expertise concerning machinery and equipment. The results also indicate the absence of marketing support mechanisms that contribute to small and medium enterprises access to new markets or global markets. The results also indicate the absence of mechanisms to support administrative cadres that contribute to the development of small and medium enterprises, as there are no mechanisms to train the workers of these Enterprise or to rehabilitate administrative leaders or to train production and marketing staff. هدفت هذه الدراسة إلى تقويم الآليات الحالية المتبعة في مجال دعم وتطوير المشروعات الصغيرة والمتوسطة في سورية من وجهة نظر أصحاب ومديري هذه المشروعات, وقد تم دراسة وتقويم آليات الدعم التمويلية والفنية والإنتاجية والتسويقية والتشريعات والسياسات الحكومية, بالإضافة إلى آليات دعم الكوادر الإدارية. وقد تم اتباع المنهج الوصفي في هذه الدراسة, وبلغ عدد الاسبانات الموزعة والصالحة للدراسة (137) استبانة, وتم تحليل البيانات باستخدام برنامج التحليل الإحصائي spss)), وأظهرت النتائج عدم ملاءمة آليات الدعم التمويلي لبدء نشاط المشروعات محل الدراسة أو توسعها, وعدم وجود تنوع بمصادر تمويل هذه المشروعات. كما أظهرت عدم قدرة آليات الدعم الفني على توفير مقومات تشييد المشروعات, أو تخفيض زمن وتكلفة تشييدها. وأظهرت أيضاً عدم توافر آليات دعم تشريعي وسياسات حكومية تسهم بتخفيف العبء المالي عن هذه المشروعات, أو تسهم بتخفيف حدة المنافسة مع المستوردات أو المشروعات الكبيرة. كما أظهرت عدم توافر آليات دعم إنتاجي تساعد على توفير المعلومات التكنولوجية المتعلقة بكل صناعة للمشروعات محل الدراسة, أو تقدم الاستشارات التقنية والخبرات التي تخص الآلات والمعدات. وبينت النتائج أيضاً عدم توافر آليات دعم تسويقي تسهم تسهم بوصول المشروعات الصغيرة والمتوسطة لأسواق جديدة أو للأسواق العالمية. كما بينت النتائج عدم توافر آليات لدعم الكوادر الإدارية تسهم بتطوير المشروعات الصغيرة والمتوسطة, حيث أنه لايوجد آليات لتدريب عمال هذه المشروعات أو لتأهيل القيادات الإدرية, أو لتدريب موظفي الإنتاج والتسويق.